Антропоморфні статуї суворівської курганної групи з Північно-Західного Криму - Ольховський, В.С. (Археологія, 1992)
Публікація присвячена скіфським антропоморфним статуям. В статье публикуются антропоморфные изваяния из курганов 11 и 13 могильников у с. Суворовского Сакского района Крыма. Изваяние из кургана 11 является плоской скульптурой и датируется IV в. до н. э., из кургана 13 — антропоморфной плитой 1-й четверти IV в. до н. э. Условия находки изваяний, особенности их формы и размещения на них изображений подтверждают и уточняют некоторые представления о скифской антропоморфной скульптуре Причерноморья. Anthropomorphous sculptures from tumuli 11 and 13 of the burial ground near the vil. Suvorovskoe of the Saki Region of the Crimea are described in the paper. The sculpture from tumulus 11 is a plane one attributed to the 4th cent. B.C., that from tumulus 13 is an anthropomorphous plate of the 1st quarter of the 4th cent. B.C. Peculiarities of the shape of the sculptures and distribution of images on them as welt as tumuli where they were found confirm and specify some ideas on the Scythian antropomorphous sculpture of the Black Sea area.